THE RELATIONSHIP BETWEEN FAMILY STRESS, DEPRESSION, AND COPING MECHANISMS IN SCHIZOPHRENIA FAMILIES - Emelda, Emelda; Fitri, Nurwijaya; Mardianna, Nova (Universitas Airlangga, 2025)
Introduction: Families play a crucial role in caring for members with schizophrenia, but the stress and depression resulting from caregiving often overshadow the coping mechanisms used. This study aims to analyze the relationship between stress, depression, and coping mechanisms in families caring for individuals with schizophrenia. Methods: A quantitative approach with a cross-sectional design was used. The sample included 59 families with members suffering from schizophrenia who were receiving treatment at the Outpatient Clinic of dr. Samsi Jacobalis Mental Hospital in Bangka Belitung Islands Province in 2024. Stress and depression were measured using the Depression Anxiety Stress Scales (DASS-42), with Cronbach's alpha values of 0.8806 for stress and 0.9053 for depression. Coping mechanisms were measured using the Brief COPE, with a reliability coefficient of 0.952. Data were analyzed using the chi-square test with SPSS software. Results: The study found that 31 individuals (52.5%) experienced severe stress, and 38 individuals (64.4%) experienced moderate depression. Additionally, 39 individuals (66.1%) exhibited maladaptive coping mechanisms. Statistical analysis revealed a significant relationship between stress and coping mechanisms (p = 0.000), and between depression and coping mechanisms (p = 0.000). Conclusions: The study concludes that there is a relationship between stress and depression with family coping mechanisms in schizophrenia patients. It is recommended that families be provided with clear information about schizophrenia, its impact, and how to care for affected members. Additionally, offering training on adaptive coping strategies, such as relaxation, mindfulness, and acceptance, may help families better manage stress and depression.